Are both classroom autonomy support and structure equally important for students' engagement? A multilevel analysis. (February 2016) - Hospel, Virginie; Galand, Benoît
Abstract: The current study was carried out within the framework of self-determination theory and aimed to investigate specific, additive and combined effects of teachers' autonomy support and structure on students' engagement. Using multilevel analyses, main effects and interaction of autonomy support and structure provided at the classroom level were tested on behavioral, cognitive and emotional engagement. 744 ninth grade students from 51 classes completed a questionnaire about their engagement during language classes and their perceptions of the teacher's provision of autonomy support and structure. The results highlight the links between classroom context, especially structure, and the three components of engagement. Autonomy support has a complementary role as it was associated with emotional engagement. These results improve our understanding of the relationships between learning environment and engagement and provide more accurate indications to teachers and educators regarding the most effective ways to enhance students' engagement. Highlights: Class context was found to be linked with individual student engagement. The teachers' practices appear to be more crucial than class composition. Teacher's structure has a pivotal role on the three components of engagement. Autonomy support has a complementary role regarding emotional engagement.